The Effect of Sleep Duration on Overweight or Obesity in Female Adolescents: A Meta-Analysis Study - Jannah, Putri Isriyatil; Pamungkasari, Eti Poncorini; Prasetya, Hanung (Indonesian Journal of Medicine, 2021)
Background: Overweight or obesity is a condition of excessive accumulation of fat in the body which is indicated by a Body Mass Index value exceeding 25 kg/m2. WHO estimated that in 2022 adolescents will experience more obesity cases than underweight cases. One of the behaviors that can reduce the risk of overweight and obesity is having adequate sleep duration. This study aimed to analyze the magnitude of the effect of sleep duration on overweight or obesity in female adolescents with a meta-analysis study.Subjects and Method: This was a systematic review and meta-analysis study. The study was carried out by following the PRISMA diagram. The process of the search for articles through a database that included: PubMed, Google Scholar, and Springer Link. The articles were selected in the period 2009-2020. The keywords used include: "sleep duration" AND adolescents, overweight AND "female adolescents", obesity AND adolescent, "sleep duration" OR "overweight obesity" OR adolescents OR "cross-sectional", "sleep duration" AND "overweight obesity "AND adolescent," sleep timing "AND obesity AND girls. The inclusion criteria were full-text articles with cross-sectional study design, English and Indonesian articles, and articles that used multivariate analysis with adjusted Odds Ratio. The articles that qualify were analyzed using the Review Manager 5.3 application.Results: A total of 9 primary articles from Korea, China, and the USA had conducted a meta-analysis with a sample of 104,726 female adolescents. The results of the meta-analysis showed that female adolescentswith short sleep duration had a risk of overweight or obesity 1.44 times compared with female adolescents with long sleep duration (aOR= 1.44, 95% CI= 1.24 to 1.69, p<0.001).Conclusion: Short sleep duration significantly increases overweight/obesity in female adolescents.Keywords: duration of sleep, overweight or obesity, female adolescentsCorrespondence: Putri Isriyatil Jannah. Masters Program in Public Health, Universitas Sebelas Maret. Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: putriisriyatil@gmail.com. Mobile: 089634956745.Indonesian Journal of Medicine (2021), 06(01): 52-61https://doi.org/10.26911/theijmed.2021.06.01.06.